The Effect of Return on Equity, Current Ratio, Risk Based Capital, and Debt to Asset Ratio on Tax Avoidance in Insurance Companies Registered on The Indonesia Financial Services Authority in 2019 – 2023 - Zahra Muslimah Mulyawan; Ahmad Zakie Mubarrok (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2025)
This study aims to determine the influence of Return on Equity, Current Ratio, Risk Based Capital, and Debt to Asset Ratio on Tax Avoidance in insurance companies listed with the Indonesia Financial Services Authority from 2019 to 2023. The study utilizes a sample of 34 conventional general insurance companies selected through purposive sampling techniques. The type of data used is secondary data obtained through the observation of financial reports of insurance companies registered and supervised by Indonesia Financial Services Authority from 2019 to 2023. Data analysis is performed using SPSS 27 software with various analysis techniques, including descriptive statistical tests, classical assumption tests, multiple linear regression analysis, determination coefficient analysis, partial hypothesis tests, and simultaneous hypothesis tests. The research results show that (1) Return on Equity has no effect on Tax Avoidance, (2) Current Ratio has a positive effect on Tax Avoidance, (3) Debt to Asset Ratio has a positive effect on Tax Avoidance, (4) Risk Based Capital has no effect on Tax Avoidance, (5) The simultaneous test shows that Return on Equity, Current Ratio, Risk Based Capital, and Debt to Asset Ratio have a simultaneous effect on Tax Avoidance.